Handbook of pragmatics : 21st annual installment - Östman, Jan-Ola; Verschueren, Jef, 1952- (Handbook of pragmatic, 2018)
"This encyclopaedia of one of the major fields of language studies is a continuously updated source of state-of-the-art information for anyone interested in language use. The IPrA 'Handbook of Pragmatics' provides easy access - for scholars with widely divergent backgrounds but with convergent interests in the use and functioning of language - to the different topics, traditions and methods which together make up the field of Pragmatics, broadly conceived as the cognitive, social and cultural study of language and communication, i.e. the science of language use. 0The 'Handbook of Pragmatics' is a reference work for researchers, which has been expanded and updated continuously with annual installments since 1995."--Resumé vydavatele